2014
DOI: 10.1371/journal.pone.0108205
|View full text |Cite|
|
Sign up to set email alerts
|

Long Term Natural History Data in Ambulant Boys with Duchenne Muscular Dystrophy: 36-Month Changes

Abstract: The 6 minute walk test has been recently chosen as the primary outcome measure in international multicenter clinical trials in Duchenne muscular dystrophy ambulant patients. The aim of the study was to assess the spectrum of changes at 3 years in the individual measures, their correlation with steroid treatment, age and 6 minute walk test values at baseline. Ninety-six patients from 11 centers were assessed at baseline and 12, 24 and 36 months after baseline using the 6 minute walk test and the North Star Ambu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
108
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 108 publications
(129 citation statements)
references
References 17 publications
12
108
0
5
Order By: Relevance
“…The previously reported age dichotomy15, 26 observed for the general DMD population was confirmed for the subpopulation of patients with genotypes amenable to exon skipping (see Fig 3A). Consistent with previous reports, patients <7 years of age showed improvement over the first 2 years of observation, followed by a decline (although remaining above the baseline value by 25m) between months 24 and 36.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…The previously reported age dichotomy15, 26 observed for the general DMD population was confirmed for the subpopulation of patients with genotypes amenable to exon skipping (see Fig 3A). Consistent with previous reports, patients <7 years of age showed improvement over the first 2 years of observation, followed by a decline (although remaining above the baseline value by 25m) between months 24 and 36.…”
Section: Resultssupporting
confidence: 79%
“…It has been previously suggested that disease severity may be affected by mutation type,25 and multiple publications have demonstrated an age‐dependent change in disease trajectory, showing that when younger than 7 years, boys with DMD experience a steady increase in 6MWT distance, whereas boys aged ≥7 years experience progressive decline 15, 26. In the current study, the pooled historical control data set was analyzed to further elucidate the effect of mutation type and age on disease progression to further the field's understanding of DMD disease progression and to identify the most comparable patient subset for comparison to the eteplirsen‐treated cohort.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Disrupted muscle NO signaling impairs muscle blood flow regulation in dystrophindeficient mice (27) and results in markedly exaggerated fatigue after exercise (28). Severe muscle fatigue is also a prominent feature of human DMD, and its improvement is considered an important clinical outcome for therapies, such that the 6-min walk test is an important endpoint for clinical trials in DMD (29). Despite growing appreciation of the physiological implications of disrupted muscle NO production, it remains unclear whether impaired nNOS activation in dystrophin-deficient skeletal muscle is a consequence of disrupted scaffolding of nNOS to the DGC, or whether the DGC acts as a mechanosensor in a mechanosignaling pathway that regulates nNOS activity.…”
mentioning
confidence: 99%